Extension of The Theory of Planned Behaviour using Buyer Behaviour Model: Halal Product Trial Model - Altekreeti, Bishr Noori Ismael; Daud, Salina (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to propose a model of Halal food product trial by integrating the factors of the buyer’s behaviour model into the Theory of Planned Behaviour (TPB). Therefore, components such as attitude, subjective norm, perceived behavioural control, Halal certification, health consciousness, and promotion were considered as the antecedents of Halal food product trial. Meanwhile, the introduction of religiosity as a moderator was to explain the manner in which Halal food product trial would be determined by Muslim consumers. This is compounded by the scarcity of studies on Halal food product trial, highlighting the need for further empirical and theoretical research pertaining to such issues faced by businesses nowadays.